Patients with spontaneous pneumothorax have a higher risk of developing lung cancer: A STROBE-compliant article. Issue 30 (24th July 2020) - Chen, Chien-Kuang; Chang, Yen-Jung; Fang, Hsin-Yuan
Abstract : Abstract: Lung cancer is a common malignancy worldwide, and risk factors include bronchitis, asthma, tuberculosis, smoking, and air pollution. These are also risk factors for spontaneous pneumothorax, a benign disease. We hypothesized that patients who experience a spontaneous pneumothorax have a greater risk to develop lung cancer, and designed a study to determine if this is so. We used the population-based Taiwan Health Insurance Research Database to perform a retrospective cohort study. The database includes more than 99% of the population of Taiwan. We established a 27, 405-person pneumothorax cohort and a 109, 620 person comparison cohort with data from 2000 to 2009 to evaluate the relationship between spontaneous pneumothorax and lung cancer. Multivariable analysis showed that patients who have had a spontaneous pneumothorax have a greater relative risk to develop lung cancer. The overall hazard ratio was 2.09 (95% confidence interval 1.69-2.58) adjusted by age, gender, hypertension, diabetes mellitus, and chronic lung diseases such as chronic obstructive pulmonary disease, tuberculosis, asthma, bronchitis, and emphysema. A dose effect was present; a high frequency of spontaneous pneumothorax was associated with a greater relative risk to develop lung cancer. If the spontaneous pneumothorax frequency was greater than 2 times per year, the hazard ratio was 34.09 (95% confidence interval 22.74-51.10) Patients with spontaneous pneumothorax have an increased relative risk to develop lung cancer, especially among patients 35 to 49 years of age. The more frequent the occurrence of spontaneous pneumothorax, the greater the relative risk of lung cancer. If the spontaneous pneumothorax frequency was greater than 2 times per year, the increase in risk of lung cancer was more than 30-fold.